Soxhlet extraction of essential oil from Zingiber from officinale and optimization of process parameters - Haidar Hassan Mohammed, 1985-; Mohd. Azizi Che Yunus, supervisor; Fakulti Kejuruteraan Kimia (2011)
Thesis (Sarjana Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2011